1967
DOI: 10.1530/jrf.0.0130031
|View full text |Cite
|
Sign up to set email alerts
|

Origin of the Antigens in Rabbit Semen Which Induce Antifertility Antibodies

Abstract: Summary. Cattle and guinea-pig antisera against rabbit testis, epididymal spermatozoa and ejaculated semen had high titres of sperm agglutinins and prevented fertilization of ova in rabbits bred with semen treated with these sera. Although cattle antisera produced against seminal plasma from vasectomized rabbits, 9-day-old-rabbit conceptuses and rabbit brain and guinea-pig antiserum to seminal plasma containing epididymal secretions exhibited relatively high titres of sperm agglutinins, none of these sera prev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
19
0

Year Published

1967
1967
1988
1988

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(23 citation statements)
references
References 13 publications
4
19
0
Order By: Relevance
“…This sterility was produced by antibodies against sperm-specific antigens rather than the sperm-coating antigens (Menge & Protzman, 1967). In the female rabbit, Weil & Roberts (1965) demonstrated that the formation of antibodies against rabbit seminal plasma had no effect on fertility.…”
Section: Discussionmentioning
confidence: 99%
“…This sterility was produced by antibodies against sperm-specific antigens rather than the sperm-coating antigens (Menge & Protzman, 1967). In the female rabbit, Weil & Roberts (1965) demonstrated that the formation of antibodies against rabbit seminal plasma had no effect on fertility.…”
Section: Discussionmentioning
confidence: 99%
“…Embryo mor¬ tality was also induced in 9-day-old rabbit embryos by direct contact with this bovine antiserum (Menge, Kiddy, Stone & Casida, 1962). Menge & Protzman (1967) (Behrman & Nakayama, 1965) and mice (McLaren, 1964 (Pierce, 1953;Kerr & Robertson, 1953;Kerr, 1955;Terpstra, 1956). The conflicts may arise partially because of a gradient phenomenon, in that unless the circulatory titre of antibody is high the amount of antibody in the secretions of the genital tract may be diluted to such an extent that it is difficult to detect.…”
Section: Discussionmentioning
confidence: 99%
“…Plank (1967) noted that few spermatozoa ever reached the oviduct in iso-immunized guinea-pigs, and those that did were immotile shortly after mating. Rabbit spermatozoa which had been incubated in vitro with heterologous anti-sperm sera were alive at the time of insemination, but failed to fertilize rabbit eggs (Menge & Protzman, 1967). It seems probable that this was due to a cytotoxic action on the antibody-sensitized sperm cells in the re¬ productive tract following contact with complement in vivo.…”
Section: Immunological Assaysmentioning
confidence: 99%